Polymer compound

A composition with specific polymer compounds forms a cured film that maintains excellent bioadhesion suppression performance in saline-exposed environments, addressing the issue of poor long-term stability in existing biocompatible materials.

JP2025063156AActive Publication Date: 2025-04-15NAT INST FOR MATERIALS SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025003989
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2041-01-25

AI Technical Summary

Technical Problem

Existing biocompatible materials used for suppressing bioadhesion, such as those described in Patent Document 1, exhibit poor long-term stability in saline-exposed environments, leading to a decline in bioadhesion suppression performance over time.

Method used

A composition comprising a first polymer compound with specific repeating units, a second polymer compound with a photoradical generating group, and a hydrophilic group, which forms a cured film that maintains excellent bioadhesion suppression performance even in saline-exposed environments for an extended period.

Benefits of technology

The composition effectively forms a cured film that sustains excellent bioadhesion suppression performance for a long duration in saline-exposed environments, ensuring the longevity of applications such as underwater structures and medical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063156000043
    Figure 2025063156000043
  • Figure 2025063156000044
    Figure 2025063156000044
  • Figure 2025063156000045
    Figure 2025063156000045
Patent Text Reader

Abstract

To provide a composition capable of forming a cured film that can maintain an excellent biofouling inhibiting ability for a long time even in a saline exposure environment.SOLUTION: A composition contains a first polymer compound with an acrylamide unit having a hydrophilic group and an acrylamide unit having a photoradical-generating group, and a second polymer compound with a repeating unit represented by the formula (3). (L1 is an amide or a phenyl group, R5 is H, a halogen, or the like, and Z3 is a group having a hydrophilic group).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a cured film, a laminate, a ship, an underwater structure, a medical device, and a microchannel chip. [Background technology]

[0002] Conventionally, coating materials for suppressing biofouling have been known. Patent Document 1 describes a coating material having a graft chain composed of a vinyl monomer and a surface occupancy rate (σ * The present invention describes a biocompatible material comprising a graft polymer in which the cross-linking ratio (R) is 0.1 or more, and at least some of the graft polymer chains are cross-linked. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-210956 A Summary of the Invention [Problem to be solved by the invention]

[0004] The biocompatible material described in Patent Document 1 has excellent biofouling inhibition performance. However, the present inventors have found that the biocompatible material has room for improvement in terms of long-term stability in a saline exposure environment.

[0005] Therefore, an object of the present invention is to provide a composition capable of forming a cured film that can maintain excellent biofouling inhibition performance for a long period of time even in a saline exposure environment. Another object of the present invention is to provide a cured film, a laminate, a ship, an underwater structure, a medical device, and a microchannel chip. [Means for solving the problem]

[0006] As a result of extensive investigations aimed at achieving the above object, the present inventors have found that the above object can be achieved by the following configuration.

[0007] [1] A composition comprising a first polymer compound having a repeating unit represented by formula 1 described below and a repeating unit represented by formula 2 described below, and a second polymer compound having a repeating unit represented by formula 3 described below. [2] The composition according to [1], wherein the content of the repeating unit represented by the above formula 2 relative to all repeating units of the first polymer compound is 10 mol % or less. [3] Z above 1 is a group represented by formula A described below. [4] The composition according to any one of [1] to [3], wherein the hydrophilic group is a hydroxy group. [5] The composition according to any one of [1] to [4], wherein the photoradical generating group is a group represented by the following formula g1: [6] The composition according to any one of [1] to [5], wherein the photoradical generating group is a group represented by the following formula g2: [7] A cured film obtained by curing the composition according to any one of [1] to [6]. [8] A laminate comprising a substrate and the cured film according to [7] formed on the substrate. [9] A ship having the cured film described in [7].

[10] An underwater structure having the cured film described in [7].

[11] The underwater structure described in

[10] , which is a pollution prevention membrane.

[12] A medical device having the cured film described in [7].

[13] The medical device according to

[12] , which is one selected from the group consisting of a cell culture vessel, a cell culture sheet, a cell capture filter, a vial, a plastic-coated vial, a syringe, a plastic-coated syringe, an ampoule, a plastic-coated ampoule, a cartridge, a bottle, a plastic-coated bottle, a pouch, a pump, a sprayer, a stopper, a plunger, a cap, a lid, a needle, a stent, a catheter, an implant, a contact lens, a microchannel chip, a drug delivery system material, an artificial blood vessel, an artificial organ, a hemodialysis membrane, a guard wire, a blood filter, a blood storage pack, an endoscope, a biochip, a glycosynthesis device, a molding auxiliary material, and a packaging material.

[14] A microchannel chip comprising a substrate and the cured film according to [7] disposed on the substrate. Effect of the Invention

[0008] According to the present invention, there is provided a composition capable of forming a cured film capable of maintaining excellent biofouling suppression performance for a long period of time even in a saline exposure environment. Furthermore, according to the present invention, there are also provided a cured film, a laminate, a ship, an underwater structure, a medical device, and a microchannel chip. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic partial cross-sectional view of a ship according to an embodiment of the present invention. FIG. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a selected substrate of a ship according to an embodiment of the present invention. [Diagram 3] 1 is a schematic diagram of an underwater structure according to an embodiment of the present invention. [Figure 4] 1 is a perspective view of a medical device according to an embodiment of the present invention. [Diagram 5] 1 is a graph showing the average film thickness of the immersion experiment results (Examples 10 and 14). [Figure 6] 1 is a graph showing the average film thickness of the immersion experiment results (Example 9, Example 13). [Figure 7] 1 is a graph showing the average film thickness of the immersion experiment results (Example 8, Example 11). [Figure 8] 1 is a graph showing the test results of biofouling inhibition performance in a saline exposure environment (immersion 0 days). [Figure 9] 1 is a graph showing the test results of biofouling inhibition performance in a saline exposure environment (immersion for one month). [Figure 10] 1 is a graph showing the test results of biofouling inhibition performance in a saline exposure environment (immersion for 2 months). [Figure 11] 13 shows images of the results of an evaluation of biofouling inhibition performance in a saline exposure environment using Cyprus larvae. [Figure 12] 1 is a graph showing the ratio of attached juvenile barnacles (per 100 seedings) in biofouling control performance in a saline exposure environment. [Figure 13] This is a captive-reared cypris larva. [Figure 14] This is an image of the entire surface of the sample at the end of the test in Example 21. The black dots in the image are juvenile barnacles attached to the sample surface. [Figure 15] 1 is an image of the entire surface of the sample at the end of the test in Example 22. [Figure 16] This is an image of the entire sample at the end of the test in Example 23. [Figure 17] This is an image of the entire sample at the end of the test in Example 24. [Figure 18] This is an image of the entire sample at the end of the test in Example 25. [Figure 19] This is an image of the entire sample at the end of the test in Example 26. [Figure 20] This is an image of the entire sample at the end of the test in Example 27. [Figure 21] This is an image of the entire sample at the end of the test in Example 28. [Figure 22] 1 is a graph showing the number of cypris larvae attached to each sample. [Diagram 23] This is an NMR chart of polyHPA bottle brush (acrylamide type, Example 15) heated in 1 M sodium hydroxide solution. [Figure 24]This is an NMR chart of polyPEGMA bottle brush (methacrylate type, Example 29) heated in 1M sodium hydroxide solution. [Diagram 25] This is an NMR chart of PolyHPA bottle brush (acrylamide type, Example 15) heated in 1 M hydrochloric acid. [Figure 26] NMR chart of PolyPEGMA bottle brush (methacrylate type, Example 29) heat-treated in 1M hydrochloric acid. [Figure 27] This is a GPC chart of polyHPA bottle brush (acrylamide type, Example 15) that underwent hydrolysis reaction in heavy water for 6 hours. [Figure 28] 1 is a GPC chart of polyHPA bottle brush (acrylamide type, Example 15) subjected to hydrolysis reaction in sodium hydroxide for 6 hours. [Figure 29] 1 is a GPC chart of polyHPA bottle brush (acrylamide type, Example 15) subjected to hydrolysis reaction in hydrochloric acid for 6 hours. [Diagram 30] 1 is a GPC chart of polyPEGMA bottle brush (methacrylate type, Example 29) subjected to a hydrolysis reaction in deuterium oxide for 6 hours. [Diagram 31] 1 is a GPC chart of polyPEGMA bottle brush (methacrylate type, Example 29) subjected to a hydrolysis reaction in sodium hydroxide for 6 hours. [Diagram 32] 1 is a GPC chart of polyPEGMA bottle brush (methacrylate type, Example 29) subjected to a hydrolysis reaction in hydrochloric acid for 6 hours. [Diagram 33] 1 is a photograph showing the state of a cured film formed on a silicon substrate using a binary copolymer (HPA / BPA=95 / 5) before and after cleaning. [Diagram 34] 1 is a photograph showing the state of a cured film formed on a silicon substrate using a terpolymer (HPA / BPA / DOPA=85 / 5 / 10) before and after cleaning. [Diagram 35] 1 is a photograph showing the appearance of a cured film formed on an aluminum substrate using a binary copolymer (HPA / BPA=95 / 5) after cleaning. [Diagram 36]1 is a photograph showing the appearance of a cured film formed on an aluminum substrate using a terpolymer (HPA / BPA / DOPA=85 / 5 / 10) after cleaning. [Figure 37] 1 is a photograph showing the appearance of a cured film formed on a silicon substrate using a binary copolymer (HPA / BPA=95 / 5) after ultrasonic cleaning. [Figure 38] 1 is a photograph showing the appearance of a cured film formed on a silicon substrate using a terpolymer (HPA / BPA / DOPA=85 / 5 / 10) after ultrasonic cleaning. [Figure 39] The number of L929 cells attached to the sample. [Diagram 40] Photograph of juvenile barnacles attached to the control at the end of the test (whole sample). [Diagram 41] This is a photograph (whole sample) of juvenile barnacles attached to a cured film of terpolymer (HPA / BPA / DOPA=85 / 5 / 10) at the end of the test. [Diagram 42] Photograph of juvenile barnacles attached to the hardened HPA / BPA / DOPA-bottlebrush film at the end of the test (whole sample). [Diagram 43] This is a photograph of juvenile barnacles (whole sample) attached to a glass plate at the end of the test. [Diagram 44] This shows the number of cypris larvae attached to each sample 9 days after the attachment test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0011] In the description of groups (atomic groups) in this specification, the description that does not indicate whether substituted or unsubstituted includes both unsubstituted and substituted groups, as long as it does not impair the effects of the present invention. For example, "alkyl group" includes not only alkyl groups that do not have a substituent (unsubstituted alkyl groups), but also alkyl groups that have a substituent (substituted alkyl groups). This also applies to each compound. In this specification, "(meth)acrylamide" refers to both or either of acrylamide and methacrylamide. Similarly, when written as "(meth)acryl", "(meth)acryloyl", or "(meth)acrylate", it refers to both or either of methacryl / acryl, methacryloyl / acryloyl, and methacrylate / acrylate, as described above.

[0012] [Composition] The composition according to an embodiment of the present invention (hereinafter also referred to as "the composition") is a composition comprising a first polymer compound having a repeating unit represented by formula 1 described below and a repeating unit represented by formula 2 described below, and a second polymer compound having a repeating unit represented by formula 3 described below. In the following description, "repeating unit" will simply be referred to as "unit", a unit represented by formula 1 will be referred to as "unit 1", a unit represented by formula 2 will be referred to as "unit 2", a unit represented by formula 3 will be referred to as "unit 3", a first polymer compound will be referred to as "P1", and a second polymer compound will be referred to as "P2".

[0013] Although the mechanism by which the film obtained from the above composition can maintain excellent biofouling inhibition performance for a long period of time even in a saline exposure environment is not necessarily clear, the present inventors speculate as follows: Note that the following mechanism is merely speculation, and even if the problem of the present invention is solved by a mechanism other than the following mechanism, it is still within the scope of the present invention.

[0014] While the biocompatible material described in Patent Document 1 has excellent performance, its biofouling suppression performance may decrease over time in a saline exposure environment, and this tendency was prominent when it contained a polymer having a (meth)acrylate structure. As a result of intensive research, the present inventors found that one of the factors that causes the biofouling suppression performance to decrease over time is that the polymer is hydrolyzed in a saline exposure environment and peels off and / or decomposes over time.

[0015] Based on the above findings, the inventors searched for a large number of polymers that have excellent hydrolysis resistance in a saline exposure environment, and as a result, they tested polymers having a (meth)acrylamide structure, and completed the invention of a composition that can form a cured film that maintains excellent biofouling inhibition performance, as shown in the examples described below. Each component contained in the composition will be described in detail below.

[0016] [P1] The composition contains P1. The content of P1 in the composition is not particularly limited, but in order to obtain a composition having better effects of the present invention, it is generally preferable that the content of P1 is 0.1 to 99.9 mass% based on the total mass of the solid content of the composition.

[0017] The composition may contain one type of P1 alone or two or more types. When the composition contains two or more types of P1, the total content is preferably within the above numerical range. P1 has a unit 1 and a unit 2. Each unit contained in P1 will be described in detail below.

[0018] <Unit 1> The content of unit 1 in P1 is not particularly limited, but in order to obtain a composition having better effects of the present invention, it is generally preferable that the content be 0.1 mol % to 99.9 mol % relative to all repeating units of P1 (hereinafter also referred to as "all units") In particular, the content of unit 1 is preferably 90 mol % or more, and more preferably 95 mol % or more, of all units in P1, in terms of obtaining a composition having better effects of the present invention. P1 may contain one type of unit 1 alone or two or more types. When P1 contains two or more types of unit 1, the total content is preferably within the above numerical range.

[0019] Unit 1 is represented by the following formula 1.

[0020] [ka]

[0021] In formula 1, R 1 represents a hydrogen atom or an alkyl group; Z 1 represents a group having a hydrophilic group. R 1 The alkyl group is not particularly limited, but is preferably an alkyl group having 1 to 10 carbon atoms. Z 1 The hydrophilic group contained in the group having a hydrophilic group (hereinafter also referred to as "hydrophilic group-containing group") is not particularly limited, and examples thereof include groups having a hydroxy group, an amino group, a carboxy group, a sulfonic acid group, a phosphonic acid group, an alkoxy group, and a zwitterionic group, etc. The zwitterionic group is not particularly limited, and examples thereof include carboxybetaine, sulfobetaine, and phosphobetaine, etc.

[0022] The hydrophilic group-containing group is not particularly limited, but a group represented by the following formula A is preferred. [ka]

[0023] In the above formula, L A represents a single bond or a p+q+1 valent group, L Brepresents a single bond or a divalent group, Y represents a hydrophilic group (such as a hydroxyl group, an amino group, a carboxyl group, a sulfonic acid group, a phosphonic acid group, an alkoxy group, or a zwitterionic group), p represents an integer of 1 or more, R 6 represents a hydrogen atom, a halogen atom, or a monovalent organic group, q represents an integer of 0 or more, and * represents a bonding position. A When is a single bond or a divalent group, p is 1 and q is 0. In formula A, there are multiple L B , R 6 and Y may be the same or different.

[0024] L A The divalent group is not particularly limited, and examples thereof include -C(O)-, -C(O)O-, -OC(O)-, -O-, -S-, -NR2- (R2 represents a hydrogen atom or a monovalent organic group), an alkylene group (preferably having 1 to 10 carbon atoms), a cycloalkylene group (preferably having 3 to 10 carbon atoms), an alkenylene group (preferably having 2 to 10 carbon atoms), an arylene group, and combinations thereof.

[0025] L A The trivalent or higher group is not particularly limited, but examples thereof include groups represented by the following formulae (3BRC) to (6BRC).

[0026] [ka]

[0027] In formula 3BRC, L3 represents a trivalent group. T3 represents a single bond or a divalent group, and three T3 may be the same or different. Examples of L3 include a nitrogen atom, a trivalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be an aromatic hydrocarbon group or an aliphatic hydrocarbon group), or a trivalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L3 include a glycerin residue, a trimethylolpropane residue, a phloroglucinol residue, and a cyclohexanetriol residue.

[0028] In formula 4BRC, L4 represents a tetravalent group. T4 represents a single bond or a divalent group, and the four T4 may be the same or different. Suitable forms of L4 include a tetravalent hydrocarbon group (preferably having 1 to 10 carbon atoms. The hydrocarbon group may be either an aromatic hydrocarbon group or an aliphatic hydrocarbon group) and a tetravalent heterocyclic group (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L4 include a pentaerythritol residue and a ditrimethylolpropane residue.

[0029] In formula 5BRC, L5 represents a pentavalent group. T5 represents a single bond or a divalent group, and five T5 may be the same or different. Suitable forms of L5 include pentavalent hydrocarbon groups (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic or aliphatic hydrocarbon group) or pentavalent heterocyclic groups (preferably a 5- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L5 include an arabinitol residue, a phloroglucidol residue, and a cyclohexanepentanol residue.

[0030] In formula 6BRC, L6 represents a hexavalent group. T6 represents a single bond or a divalent group, and six T6 may be the same or different. Suitable forms of L6 include a hexavalent hydrocarbon group (preferably having 2 to 10 carbon atoms. The hydrocarbon group may be an aromatic or aliphatic hydrocarbon group) or a hexavalent heterocyclic group (preferably a 6- to 7-membered heterocyclic group), and the hydrocarbon group may contain a heteroatom (e.g., -O-). Specific examples of L6 include a mannitol residue, a sorbitol residue, a dipentaerythritol residue, a hexahydroxybenzene residue, and a hexahydroxycyclohexane residue.

[0031] In the formulae 3BRC to 6BRC, specific examples and preferred forms of the divalent groups represented by T3 to T6 are the same as those of L A may be the same as the divalent group represented by the formula: Also, L A When is a group with a valence of 7 or more, a group formed by combining the groups represented by formulae 3BRC to 6BRC can be used.

[0032] In formula A, L B The divalent group of L is not particularly limited. A The divalent groups are the same as those of the divalent groups of R 6 The monovalent organic group is not particularly limited, and examples thereof include monovalent hydrocarbon groups which may have a heteroatom, and more specifically, examples of such groups include linear, branched, or cyclic alkyl groups having 1 to 10 carbon atoms.

[0033] The unit 1 is preferably a unit based on a monomer represented by the following formula 1'.

[0034] [ka]

[0035] In formula 1′, R 1 and Z 1 are the same as the respective symbols in formula 1, and the preferred embodiments are also the same.

[0036] In particular, from the viewpoint of obtaining a coating film having superior adhesion to metal substrates, silicon substrates, and the like, it is preferable that P1 contains two or more types of unit 1. When P1 contains two or more types of unit 1, P1 preferably contains a unit represented by the following formula 1A (unit 1A) and a unit represented by the following formula 1B (unit 1B).

[0037] [ka]

[0038] In formula 1A and formula 1B, L C , and L D are linear or branched alkylene groups having 1 to 6 carbon atoms, which may be the same or different from each other, r is an integer of 1 to 3, R 1 is R in Eq. 1 The same applies to the preferred embodiments.

[0039] When P1 contains units 1B, the resulting cured film has excellent adhesion to metal substrates such as aluminum and titanium, and silicon substrates (hereinafter also referred to as "metal substrates, etc.").

[0040] The contents of units 1A and units 1B in unit 1 (in other words, the composition of unit 1) are not particularly limited, but from the viewpoint of having better adhesion to metal substrates, etc., the mass ratio of the content of units 1B to the content of units 1A in P1 (1B / 1A) is preferably 0.01 to 0.4.

[0041] Unit 1 can be synthesized using a monomer having a hydroxy group-containing group such as N-(2-hydroxyethyl)acrylamide, N-(hydroxymethyl)acrylamide, and N-(2-hydroxypropyl)acrylamide; a monomer having a carboxy group-containing group such as 6-acrylamidohexanoic acid; a monomer having a zwitterion-containing group such as 3-[(3-acryloylaminopropyl)dimethylammonio]propanoate; a monomer having an alkoxy group-containing group such as N-(butoxymethyl)acrylamide; a monomer having an amino group-containing group such as N-[3-(dimethylamino)propyl]acrylamide and N-(3-dimethylaminopropyl)methacrylamide; a monomer having a sulfonic acid group-containing group such as 2-acrylamido-2-methylpropanesulfonic acid; and the like.

[0042] Furthermore, the monomer for obtaining unit 1 can be easily synthesized by a known method, such as reacting a compound having an amino group and a hydroxy group (e.g., dopamine) with a (meth)acrylic acid chloride in the presence of a base catalyst to form an amide bond.

[0043] <Unit 2> P1 has unit 2. Unit 2 has a photoradical generating group and generates radicals by irradiation with light, so it functions as a photoradical initiator fixed in the molecule. Note that unit 2 means a repeating unit different from unit 1. The content of unit 2 in P1 is not particularly limited, but is generally preferably 0.1 to 10 mol % based on the total units of P1, in order to obtain a composition having better effects of the present invention. P1 may contain one type of unit 2 alone or two or more types. When P1 contains two or more types of unit 2, the total content is preferably within the above numerical range.

[0044] Unit 2 is represented by the following formula 2.

[0045] [ka]

[0046] In formula 2, R 2 represents a hydrogen atom or an alkyl group, Z 2 R represents a photoradical generating group. 2 The alkyl group is not particularly limited, but is preferably an alkyl group having 1 to 10 carbon atoms.

[0047] Z 2 The photoradical generating group refers to a group capable of generating radicals upon irradiation with light (ultraviolet rays, radiation, etc.). As the photoradical generating group, a group derived from a known photoradical generator can also be used. Examples of the photoradical generating group include a group having a structure in which the α-position of a carbonyl is photocleaved, and a group having an oxime ester structure. In addition, in terms of obtaining a composition having a more excellent effect of the present invention, the photoradical generating group is preferably a group represented by the following formula (g1).

[0048] [ka]

[0049] In formula g1, R 7 represents an arylene group having 6 to 30 carbon atoms which may have a substituent, R 8 represents an aryl group having 6 to 30 carbon atoms which may have a substituent, and * represents the bonding position. R 7 is preferably a phenylene group, and R 8 In other words, the photoradical generating group is preferably a group represented by the following formula g2. [ka]

[0050] In formula g2, * represents a bonding position.

[0051] Unit 2 is preferably a unit based on a monomer represented by the following formula 2'.

[0052]

Chemical formula

[0053] In formula 2', R 2 and Z 2 are respectively synonymous with each symbol in formula 2, and the preferred forms are the same.

[0054] The method for producing the above monomer is not particularly limited. For example, it can be produced by reacting a photopolymerization initiator having an amino group with (meth)acrylic acid halide. The above monomer is not particularly limited. For example, N-(4-benzoylphenyl)(meth)acrylamide and the like can be mentioned.

[0055] <Method for producing P1> The method for producing P1 is not particularly limited. For example, a composition containing the monomers represented by formula 1' and formula 2' can be prepared and copolymerized by a known method. Specifically, a polymerizable composition containing a monomer represented by the following formula, a radical polymerization initiator, a solvent, etc. can be prepared and polymerized by applying energy (heating, light irradiation, etc.).

[0056] As the photopolymerization initiator, a known compound that can generate active radicals by light irradiation can be used. Examples of the photopolymerization initiator include halogenated hydrocarbon derivatives (for example, those having a triazine skeleton, those having an oxadiazole skeleton, and those having a trihalomethyl group, etc.); acylphosphine compounds such as acylphosphine oxide; oxime compounds such as hexaarylbiimidazole and oxime derivatives; organic peroxides; sulfur-containing compounds; ketone compounds; aromatic onium salts; aminoacetophenone compounds; azo compounds; azide compounds; and the like.

[0057] In addition, the polymerizable composition may contain a chain transfer agent and a polymerization inhibitor in addition to the above.

[0058] The molecular weight of P1 is not particularly limited, but the number average molecular weight (Mn) is typically preferably 10,000 to 1,000,000. The molecular weight distribution (molecular weight dispersity index: PDI) is not particularly limited, but typically preferably 1.0 to 3.0. The number average molecular weight and molecular weight distribution refer to values ​​measured using gel permeation chromatography under the conditions described below.

[0059] [P2] The composition contains P2. The content of P2 in the composition is not particularly limited, but in order to obtain a composition having better effects of the present invention, it is generally preferably 0.1 to 99.9 mass% based on the total mass of the solid content of the composition. The composition may contain one type of P2 alone or two or more types. When the composition contains two or more types of P2, the total content is preferably within the above numerical range. P2 has unit 3. Each unit of P2 will be described in detail below.

[0060] <Unit 3> P2 has units 3. The content of units 3 in P2 is not particularly limited, but is generally preferably 50 to 100 mol % based on the total units of P2, in order to obtain a composition having better effects of the present invention. P2 may contain one type of unit 3 alone or two or more types. When P2 contains two or more types of unit 3, the total content is preferably within the above numerical range. In addition, P2 may have a unit other than the unit 3.

[0061] Unit 3 is represented by the following formula 3.

[0062] [ka]

[0063] In formula 3, R3 , and R 4 each independently represents a hydrogen atom or an alkyl group, and may be the same or different; Z 3 represents a hydrophilic group-containing group, R 5 represents a hydrogen atom, a halogen atom, or a monovalent substituent; L 1 represents a group represented by formula 4a or 4b, L 2 represents a single bond or a divalent group, and in formula 4a and formula 4b, * represents a bonding position, and n represents an integer of 1 or more.

[0064] [ka]

[0065] R 3 , and R 4 The alkyl group is not particularly limited, but is preferably an alkyl group having 1 to 10 carbon atoms. Also, Z 3 is not particularly limited, Z in formula 1 1 The same groups as those mentioned above and preferred embodiments are also the same. R 5 The monovalent substituent of is not particularly limited, and examples thereof include an alkyl group, a hydroxyl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, a heteroarylthioether group, and an amino group. 5 is preferably a halogen atom. Also, L 2 The divalent group is not particularly limited, but examples thereof include hydrocarbon groups having 1 to 10 carbon atoms which may have a heteroatom, and more specifically, alkylene groups having 1 to 10 carbon atoms.

[0066] (Structure of P2) P2 has unit 3, and the unit 3 is a unit having a polymer chain as a side group in a repeating unit. Since unit 3 constitutes at least a part of the main chain of P2, the polymer chain is a side chain bonded to the main chain, and P2 is a graft polymer. The three-dimensional structure of P2 is not particularly limited, but in terms of having a superior biofouling inhibitory performance, it is preferable to use a surface occupancy rate (σ * ) is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, particularly preferably 0.4 or more, and most preferably more than 0.4. In this specification, the surface area coverage (σ * ) is 0.1 or more.

[0067] Here, the term "polymer brush" refers to an assembly of polymer chains extending from the surface of the fiber in a direction approximately perpendicular to the longitudinal direction of the short fiber, and means a plurality of graft chains bonded to the main chain of the graft polymer.

[0068] Concentrated polymer brushes are described in detail in Reference 1 (Tsujii Y et al., “Structure and Properties of High-Density Polymer Brushes Prepared by Surface-Initiated Living Radical Polymerization.”, Adv Polym Sci., Vol. 197, pp. 1-45, 2006.).

[0069] Figure 10 in Reference 1 shows the degree of extension of the grafted chains versus the grafting density, indicating that the degree of extension of the grafted chains in a "concentrated polymer brush" is greater than that in a semi-dilute system. Generally, isolated polymer chains in a good solvent take a random coil shape due to the excluded volume effect, but it is known that they take a mushroom-like shape when one end is fixed to a solid. When the surface density of the grafted chains increases, the molecular chains overlap each other, increasing the density, so it is known that the mushroom-shaped molecular chains extend in the height direction to avoid this (scaling law).

[0070] However, high surface coverage (high σ *In the region where the degree of extension of the grafted chains is experimentally confirmed to be greater than this theoretical prediction, specifically, in the region where the surface occupancy is greater than σ * means a polymer brush with a value of 0.1 or more, and σ * is preferably 0.2 or more, more preferably 0.3 or more, even more preferably 0.4 or more, and particularly preferably more than 0.4.

[0071] In addition, the surface occupancy rate (Dimensionless graft density (σ * )) means the value of the graft density normalized by the cross-sectional area of ​​the monomer, and is defined as in Reference 1.

[0072] In concentrated polymer brushes formed from such graft chains that are close to extended chains, the flexible polymer chains are in a state in which they are highly oriented as if they were rigid molecules. Compared to semi-dilute systems, they are known to have the following unique properties: (1) a large swollen film thickness (extended orientation) comparable to the extended chain length and high compression resistance; (2) a clear size exclusion effect (molecules above a certain size are not incorporated into the brush layer) both in the molten state and in solvents due to the large osmotic pressure and highly extended molecular chain morphology; and (3) no interpenetration occurs between homogeneous brushes, resulting in an extremely low friction coefficient between swollen brushes.

[0073] Specifically, the surface area coverage (σ * ) is expressed by the formula: surface occupancy rate (σ * ) = {Volume per repeating unit of the polymer chain (nm 3 / chain) / length of repeating unit of polymer chain portion (nm)}×σ(chain / nm 2 )

[0074] In the above formula, σ is the effective graft density (chains / nm 2 ).

[0075] The graft polymer P2 has a main chain and multiple polymer chains that radiate from the main chain, forming a concentrated polymer brush. The surface occupancy is a parameter that describes the area of ​​the polymer chains in the area of ​​a cylindrical surface, with the main chain of P2 as the central axis and the length of the polymer chain as the radius.

[0076] A larger surface occupancy means that the proportion of the area of ​​the imaginary cylindrical surface that is derived from the polymer chains increases, which is presumably why the degree of freedom of the polymer chains decreases and the polymer chains tend to maintain a state in which they are approximately perpendicular to the main chain of P2 and the cylindrical surface.

[0077] On the other hand, when the grafting efficiency is lower (described later) and when the polymer chain is longer (in other words, when the degree of polymerization of the polymer chain portion is higher), the density of the polymer chains on the imaginary cylinder surface decreases. In such cases, the degree of freedom of the polymer chains becomes higher and the polymer chains can be folded freely. Next, the surface area coverage (σ * ) Each term in the calculation formula will be explained in detail below.

[0078] Effective graft density (σ eff ) First, the effective graft density (σ eff ) represents the number of grafted chains per unit area of ​​the virtual cylindrical surface.

[0079] Formula: σ eff (chain / nm 2 )=1 / {(2π×α×degree of polymerization of grafted chain portion)×(α′ / grafting efficiency)}

[0080] In the above formula, α is the length (nm) of the repeating unit of the graft chain portion, and α' is the length (nm) of the repeating unit of the main chain. The method for calculating the length of the repeating unit of the polymer chain portion will be described later. eff The calculation method is as described in the Examples.

[0081] In addition, the degree of polymerization of the polymer chain portion of P2 can be determined by preparing a polymer (hereinafter also referred to as a "specific polymer") that would form a polymer chain if bound to P2 under the same conditions as when synthesizing P2, and measuring its degree of polymerization. More specifically, when synthesizing P2, a specific polymer is obtained using a compound (hereinafter also referred to as an "initiating point compound") that has one group (reactive group) that can react with a monomer for forming a polymer chain and does not constitute (does not polymerize) the main chain of P2, and the degree of polymerization of the specific polymer is then measured.

[0082] Since the specific polymer is considered to have the same degree of polymerization, number average molecular weight, and molecular weight distribution as the polymer chain portion of P2, the degree of polymerization of the specific polymer is taken as the degree of polymerization of the polymer chain portion of P2.

[0083] At this time, the number average molecular weight (Mn) and molecular weight distribution (PDI) of the specific polymer are also determined, so that the number average molecular weight and molecular weight distribution of the polymer chain portion of P2 can also be determined. Here, Mn and PDI are measured in terms of polystyrene using gel permeation chromatography (GPC) under the following conditions 1 or 2.

[0084] Condition 1 (DMF type) Column: Shodex LF804 (300 x 80 mm; bead size = 6 μm) Flow rate: 0.8ml / min (40℃) Eluent: 10mM lithium chloride in dimethylformamide (DMF)

[0085] Next, the "grafting efficiency" is the molar ratio of units having polymer chains to the total units of P2. In other words, it is the number of polymer chains per repeating unit of P2.

[0086] All units of P2 are units Pm 1 The units without a polymer chain are classified into units Pm that have a reactive group but have not reacted.2 and a unit Pm having no reactive group 3 In other words, P2 is classified into the above Pm 1 , Pm 2 , and Pm 3 Using this, it is expressed as follows:

[0087] [ka]

[0088] In the above formula, n1, n2, and n3 represent the molar ratio of each unit, n1 represents a number greater than 0, and n2 and n3 represent numbers of 0 or greater. Here, the grafting efficiency can be expressed as n1 / (n1+n2+n3) using the above symbols.

[0089] The grafting efficiency is the ratio of units having reactive groups (Pm 1 and Pm 2 ) content of units reacted with polymer chains (Pm 1 The initiation efficiency (n1 / (n1+n2)) indicates the molar ratio of the content of the reactive groups to the total units of P2, and the ratio of the units having (and having had) reactive groups (Pm 1 , Pm 2 ) is calculated from the molar ratio ((n1+n2) / (n1+n2+n3)) of the content of each of the elements.

[0090] The molar ratio of the units having a reactive group to the total units of P2 can be obtained by NMR (Nuclear Magnetic Resonance) measurement of the main chain before bonding with the polymer chain.

[0091] The initiation efficiency can be calculated based on the polymerization rate determined from the measured values ​​by NMR and GPC. The polymerization rate is determined by measuring the content of the unit having a polymer chain and the ratio of the solvent and the unreacted monomer using NMR, and is calculated as the ratio of the molar amount of the monomer bonded to the polymer chain to the molar amount of the monomer charged in the polymerization reaction. The polymerization rate can also be calculated from the peak area of ​​GPC.

[0092] Specifically, the polymerization rate of a specific polymer is calculated from the peak area of ​​GPC, and the polymerization rate assuming 100% initiation efficiency is calculated using GPC from the charge ratio of the main chain polymer and the initiation compound. Next, the content of the unit having a polymer chain in P2 and the ratio of the solvent and the unreacted monomer are measured using NMR, and the polymerization rate by NMR is calculated as the ratio of the molar amount of the monomer that contributed to the formation of the polymer chain to the molar amount of the monomer used. The polymerization rate by NMR is compared with the approximate value of the polymerization rate by GPC to determine the initiation efficiency.

[0093] The degree of polymerization of the polymer chain portion can be calculated from the thus determined initiation efficiency of P2, the polymerization rate (polymerization rate by NMR), and the molecular weight of the monomer unit constituting the graft chain.

[0094] The degree of polymerization of the polymer chain portion can also be determined by determining the absolute molecular weight of the bottle-brush polymer by GPC equipped with a time-of-flight mass spectrometer (TOF-MASS) or a multi-angle light scattering device (MALLS) and calculating the ratio with the monomer unit.

[0095] The grafting efficiency is not particularly limited, but is preferably 0.3 or more, more preferably 0.4 or more, in terms of a higher surface occupancy rate. The upper limit is not particularly limited, but is generally preferably 1 or less.

[0096] Volume per repeating unit of the polymer chain (nm 3 / chain) Volume per repeating unit of the polymer chain (v0 [nm 3 / chain) is calculated using the following formula:

[0097] V0 = {Molecular weight of the monomer in the polymer chain part / Avogadro's constant} / (Bulk density of the monomer in the polymer chain part)

[0098] In the above formula, the bulk density of the monomer in the polymer chain part means the bulk density at room temperature of the raw material (monomer) used to form the polymer chain.

[0099] · Length of the repeating unit in the polymer chain part (nm) · The length of the repeating unit in the polymer chain part is determined by GPC (gel permeation chromatography, in terms of standard polystyrene). For example, the length of the unit based on a vinyl bond is 0.25 nm.

[0100] The surface occupancy rate is a parameter that reflects the degree of freedom of the polymer chain. When the surface occupancy rate is higher, the structural degree of freedom of the polymer chain is restricted, and it is considered that the polymer chain is more likely to maintain a state of extending in a direction substantially perpendicular to the main chain. By the polymer chain extending in a direction substantially perpendicular to the main chain, in the above virtual cylindrical surface, the polymer chain is more likely to adopt a structure standing perpendicular to the main chain, and it is presumed that a more excellent effect of the present invention can be obtained. More specifically, a surface where the polymer chains are more densely packed is presumed to have less "room" for adhesion of proteins and the like that are considered to cause biofouling, and as a result, biofouling is more suppressed.

[0101] <Other units> P2 may have units other than unit 3. The other units are not particularly limited, and examples include units having a polymerizable group, and units having a hydrophilic group or a hydrophobic group. When P2 has a polymerizable group, the adhesiveness to the substrate is further enhanced when forming a film.

[0102] <Manufacturing method of P2> The method for producing P2 is not particularly limited, and known production methods can be applied. For example, a method of synthesizing a macromonomer having a predetermined polymer chain and a polymerizable group (e.g., an ethylenically unsaturated group) and then polymerizing the macromonomer to form a graft, and a "graft from" method described later can also be used.

[0103] As a method for producing P2, it is preferable to use a graft polymerization method by an atom transfer radical polymerization method (ATRP) in that a composition having a more excellent effect of the present invention can be obtained.

[0104] The ATRP method is a type of radical polymerization characterized by the fact that an active species having a propagating radical (e.g., a functional group having a radical terminal) and a dormant species capped with a halogen atom (e.g., a functional group having a halogenated terminal) are in equilibrium, and the equilibrium is heavily biased toward the dormant species, suppressing the number of active species and promoting the propagation reaction in which the active species react with monomers to grow larger, while suppressing the termination reaction.

[0105] In normal radical polymerization, in addition to the propagation reaction in which active radicals react with monomers, termination reactions such as recombination in which radicals bond with each other, disproportionation in which radicals form bonds within a molecule, and chain transfer in which radicals move to a solvent or the like can occur. One of the reasons for such termination reactions is thought to be an increase in the number of active species (radicals). Furthermore, under conditions in which termination reactions occur, it is difficult to control the molecular weight of the resulting polymer, and the molecular weight distribution tends to be broad. In addition, the terminal structure of the resulting polymer is difficult to control because it differs depending on the termination reaction.

[0106] In ATRP, the equilibrium with the active species, which is largely biased toward dormant species, suppresses the termination reaction, making it possible to obtain polymers with a narrow molecular weight distribution. In addition, since the ends of the polymers obtained by ATRP are dormant species, even if the propagation reaction has once terminated, the propagation reaction will proceed again if the reaction conditions are met again. This characteristic makes it easy to obtain polymers with the desired structure.

[0107] More specifically, as shown in the following reaction scheme, a polymer (b) (hereinafter also referred to as a "macroinitiator") based on a monomer having an ethylenically unsaturated group and a halogenated alkyl group is obtained (Scheme 1), and then a polymer chain is synthesized by a so-called "grafting from" method using the carbon radical generated by eliminating a halogen atom as an active site (Scheme 2).

[0108] [ka]

[0109] R in Scheme 1 3 , L 1 , and L 2 has the same meaning as each symbol in the formula 3 already explained, and the preferred embodiments are also the same. X represents a halogen atom, and is preferably a chlorine atom or a bromine atom. In Scheme 1, the method of polymerizing the monomer represented by (a) to obtain (b) is not particularly limited, and any known polymerization method can be applied. Among them, it is preferable to use the reversible addition-fragmentation chain transfer (RAFT) polymerization method, since it can obtain a composition having a more excellent effect of the present invention.

[0110] The RAFT method is a living radical polymerization method in which a compound capable of reversibly causing an addition-fragmentation-chain transfer reaction is used as a chain transfer agent (hereinafter referred to as a RAFT agent) to carry out polymerization. The RAFT agent is not particularly limited, and for example, various thiocarbonylthio compounds described in WO 98 / 01478, WO 99 / 31144, and WO 00 / 75207 can be used.

[0111] [ka]

[0112] R in Scheme 2 3 , R 4, L 1 , L 2 , and Z 3 are the same as the symbols in formula 3 already explained, and the preferred embodiments are also the same. X represents a halogen atom, and is preferably a chlorine atom or a bromine atom. Mt represents a metal ion, and L represents a ligand.

[0113] The metal ions and ligands generate radicals by abstracting halogen atoms from the halogenated alkyl groups that serve as reaction initiation points, and also form an equilibrium with the dormant species, thereby exerting the effect of suppressing the termination reaction of the radicals.

[0114] The metal ion is not particularly limited, and examples thereof include ions of copper, titanium, iron, cobalt, nickel, molybdenum, and ruthenium. Among them, copper ions are preferred from the viewpoint of reaction rate and the like. The metal ion is generally mixed in the form of a metal salt when preparing the reaction solution. The metal salt is not particularly limited, and examples thereof include copper chloride (I), copper chloride (II), copper bromide (I), copper bromide (II), and copper iodide (I) when the metal ion is a copper ion.

[0115] The metal salt forms a metal complex in the presence of a specific ligand, and abstracts a halogen from an alkyl halide group to generate an initiating radical. The initiating radical and the propagating radical are in equilibrium with each other as active species and dormant species, and the termination reaction is greatly suppressed. The ligand is not particularly limited, and may be appropriately selected depending on, for example, the type of metal ion used to form the complex. When copper ions are used as metal ions, nitrogen-containing ligands are useful for complex formation. In addition, the binding constant with the metal ion varies depending on the structure of the ligand, so that the rate of generation of the initiation radical and the equilibrium constant between the dormant and active species change, and the ratio of the active species to the dormant species changes, which may result in a difference in the rate of graft polymerization.

[0116] Examples of the ligand include 2,2'-dipyridyl, 4,4'-dimethyl-2,2'-dipyridyl, 4,4'-ditertiarybutyl-2,2'-dipyridyl, 4,4'-dinonyl-2,2'-dipyridyl, N-butyl-2-pyridylmethanimine, N-octyl-2-pyridylmethanimine, N-dodecyl-N-(2-pyridylmethylene)amine, N-octadecyl-N-(2-pyridylmethylene)amine, N,N,N',N'',N''- Examples of the amine include pentamethyldiethylenetriamine, tris(2-pyridylmethyl)amine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, tris[2-(dimethylamino)ethyl]amine, 1,4,8,11-tetraazacyclotetradecane, 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane, and N,N,N',N'-tetrakis(2-pyridylmethyl)-ethylenediamine.

[0117] The method for preparing the reaction solution is not particularly limited, but examples include a method in which each raw material is mixed in water, thoroughly mixed and stirred, and each component is dissolved to form an aqueous solution, and then unnecessary oxygen in the aqueous solution is removed by bubbling an inert gas or degassing under reduced pressure.

[0118] [Other ingredients] The composition may contain other components in addition to those described above within the scope of the effects of the present invention, such as copper pyrithione, zinc oxide, a rosin compound, a copper compound, a coloring pigment, an extender pigment, a pigment dispersant, a plasticizer, an anti-sagging agent, an anti-settling agent, a dehydrating agent, and a solvent.

[0119] When the present composition contains copper pyrithione, the content is not particularly limited, but is preferably 0.01 to 500 parts by mass when the total content of P1 and P2 in the composition is 100 parts by mass. The film obtained by using the present composition containing copper pyrithione has better biofouling suppression performance.

[0120] When the present composition contains zinc oxide, the content is not particularly limited, but is preferably 0.01 to 1000 parts by mass when the total content of P1 and P2 in the composition is 100 parts by mass. A film obtained by using the present composition containing zinc oxide has superior strength and superior biofouling inhibition performance.

[0121] When the present composition contains a rosin compound, the content is not particularly limited, but is preferably 0.1 to 70 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the rosin compound include rosins such as gum rosin, wood rosin, and tall oil rosin, hydrogenated rosin, and rosin derivatives such as disproportionated rosin. The present composition containing a rosin compound has better biofouling suppression performance.

[0122] When the composition contains a copper compound, the content is not particularly limited, but is preferably 0.01 to 2500 parts by mass when the total content of P1 and P2 in the composition is 100 parts by mass. Examples of the copper compound include cuprous oxide, copper thiocyanate, and cupronickel. The films obtained using the present compositions containing copper compounds have better strength and better biofouling control performance.

[0123] When the composition contains a color pigment, the content is not particularly limited, but is preferably 0.01 to 100 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the color pigment include organic pigments and inorganic pigments, and specific examples thereof include carbon black, naphthol red, phthalocyanine blue, red iron oxide, baryte powder, titanium white, and yellow iron oxide. Films obtained using the present compositions containing color pigments have better color tone.

[0124] When the composition contains a body pigment, the content is not particularly limited, but is preferably 0.01 to 100 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the body pigment include talc, silica (diatomaceous earth, acid clay, etc.), mica, clay, potassium feldspar, calcium carbonate, kaolin, alumina white, white carbon, aluminum hydroxide, magnesium carbonate, barium carbonate, barium sulfate, and zinc sulfide. Films obtained using the present compositions containing extender pigments have better mechanical properties.

[0125] When the composition contains a pigment dispersant, the content is not particularly limited, but is preferably 0.1 to 100 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the pigment dispersant include aliphatic amines or organic acids (e.g., "Duomin TDO" (manufactured by LION Co., Ltd.) and "Disperbyk101" (manufactured by BYK Co., Ltd.)). When the present composition contains a pigment dispersant, it becomes easier to adjust the viscosity of the composition, resulting in improved handleability.

[0126] When the composition contains a plasticizer, the content is not particularly limited, but is preferably 0.1 to 300 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the plasticizer include chlorinated paraffin, petroleum resins, ketone resins, TCP (tricresyl phosphate), polyvinyl ethyl ether, and dialkyl phthalate. The film obtained using the present composition containing a plasticizer has better crack resistance.

[0127] When the composition contains an anti-sagging agent, the content is not particularly limited, but is preferably 0.1 to 100 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the anti-sagging agent include amide wax, hydrogenated castor oil wax, and synthetic fine silica (Aerosil (registered trademark), etc.). The present composition containing an anti-sagging agent reduces the occurrence of "sagging" when applied to a substrate.

[0128] When the composition contains an anti-settling agent, the content is not particularly limited, but is preferably 0.1 to 100 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the anti-settling agent include stearates of Al, Ca, or Zn, polyethylene wax, and oxidized polyethylene wax. The present compositions containing anti-settling agents exhibit less settling.

[0129] When the composition contains a dehydrating agent, the content is not particularly limited, but is preferably 0.1 to 50 parts by mass when the total content of P1 and P2 is 100 parts by mass. Examples of the dehydrating agent include inorganic dehydrating agents such as synthetic zeolite, anhydrous gypsum, and hemihydrate gypsum, and organic dehydrating agents such as alkoxysilane, polyalkoxysilanes, and alkyl orthoformate. The present compositions containing a dehydrating agent have better storage stability.

[0130] When the composition contains a solvent, the content is not particularly limited. In one embodiment, the content of the solvent is preferably adjusted so that the solid content of the composition is 5 to 95 mass%. Examples of the solvent include water and organic solvents, and examples of the organic solvent include alcohol-based solvents such as methanol, ethanol, and isopropanol.

[0131] <Method of preparing the composition> The method for preparing the composition is not particularly limited, and each component described above may be mixed. In this case, the order in which each component is mixed is not particularly limited, and the components may be mixed in any order. In addition, when the composition contains a sagging inhibitor, it is preferable to first mix the other components, homogenize them, and then add the sagging inhibitor. The mixing method is not particularly limited, and a high-speed disperser, a sand grind mill, a basket mill, a ball mill, a three-roll mill, a Ross mixer, a planetary mixer, or the like can be used.

[0132] <Uses of the composition> The cured film obtained by using this composition has excellent biofouling suppression performance. For example, this composition can be used to form a cured film on a substrate to which biofouling should be prevented, in other words, to manufacture a laminate having a substrate and a cured film formed on the substrate. In particular, it is preferable to use this composition to form a cured film on a substrate that is used in contact with salt water (seawater, body fluids of organisms, etc.).

[0133] Examples of the substrate include water supply and drainage outlets of power plants (thermal and nuclear), coastal roads, undersea tunnels, underwater structures such as sludge diffusion prevention membranes used in marine civil engineering works, ship shell panels (particularly the waterline to the bottom of the ship), and fishing materials (ropes, fishing gear such as fishing nets, buoys, etc.). Examples of the substrate include cell culture vessels, cell culture sheets, cell capture filters, vials, plastic-coated vials, syringes, plastic-coated syringes, ampoules, plastic-coated ampoules, cartridges, bottles, plastic-coated bottles, pouches, pumps, sprayers, stoppers, plungers, caps, lids, needles, stents, catheters, implants, contact lenses, microchannel chips, drug delivery system materials, artificial blood vessels, artificial organs, hemodialysis membranes, guard wires, blood filters, blood storage packs, endoscopes, biochips, glycosynthesis equipment, molding auxiliary materials, and packaging materials.

[0134] [Cured film] The cured film according to the embodiment of the present invention is a film obtained by curing the composition already described. The method for producing the cured film is not particularly limited, but the composition layer can be formed on a flat plate or a three-dimensional substrate having a curved surface using the composition, and the composition layer is dried to produce the cured film. From the viewpoint of having a better biofouling suppression performance, it is preferable to cure the composition layer by irradiating it with light. The wavelength of the light irradiation is not particularly limited, but it is preferable to irradiate ultraviolet light in the wavelength range of 300 to 400 nm, more preferably around 360 nm.

[0135] Since P1 has a photoradical generating group, when the composition layer is irradiated with light, an active radical is generated, P2 is fixed to P1, and a cured film is obtained. When the photoradical generating group is a group represented by formula g2 (benzophenone), an active radical is generated by irradiation with ultraviolet light having a wavelength of 250 to 365 nm, and this generates a covalent bond by abstracting hydrogen from a hydrocarbon (for example, a partial structure of P2). Through the mechanism described above, P2 is fixed to P1, resulting in a hardened film.

[0136] Furthermore, the adhesion between the substrate and the cured film is further improved by the reaction between the active radicals and the substituents (such as hydroxyl groups and carboxyl groups) on the surface of the substrate, which will be described later.

[0137] The substrate is not particularly limited, but examples thereof include metals such as steel and aluminum, wood, and resin.

[0138] The method of forming the composition layer is not particularly limited, and includes a method of coating the composition on a substrate. The coating method is not particularly limited, and a known method can be used. Examples of the coating method include spray coating and roller coating. In addition, a method of impregnating a substrate with the composition can also be used. Alternatively, the composition layer may be formed in advance on a temporary substrate, and the composition layer formed on the temporary substrate may be attached to the substrate.

[0139] [Ship] FIG. 1 is a schematic partial cross-sectional view of a ship according to an embodiment of the present invention, and FIG. 2 is a schematic cross-sectional view of a bottom base material thereof. In FIG. 1, the bottom shell plate of a ship 10 is a laminate having a metal substrate 11, a primer layer 12 disposed on the substrate 11, and a cured film 13 disposed on the primer layer. Since the ship has the cured film on its outer plate, adhesion of aquatic organisms such as sea lettuce, barnacles, green laver, cerpula, oysters, and hairy bryozoans can be inhibited for a long period of time.

[0140] Although the above-mentioned ship has a primer layer, the ship according to the embodiment of the present invention is not limited to the above and may not have a primer layer. In addition, another layer may be further provided between the substrate and the cured film.

[0141] [Underwater structures] 3 is a schematic diagram of an underwater structure according to an embodiment of the present invention. The underwater structure 20 includes a float 21 arranged on the sea surface SL, a curtain 22 fixed to the float 21 and hanging down from the float 21 into the sea, a weight 23 fixed to the lower end of the curtain 22, an anchor rope 25 for connecting the float 21 to an anchor 24 arranged on the seabed OF, and a buoy 26 arranged on the sea surface SL and placed midway on the anchor rope 25 to avoid contact between the curtain 22 and the anchor rope 25.

[0142] The underwater structure 20 is typically a pollution prevention membrane that is placed in the sea and is used to promote the sinking of pollution particles and suppress the diffusion of pollution. Of these, the curtain 22 is a portion for preventing the diffusion of contamination, and is made of a polyester fiber woven fabric as a base material, on which the cured film is disposed. Therefore, even if the curtain 22 is placed in water for a long period of time, adhesion of organisms to the curtain 22 is easily suppressed.

[0143] The float 21 and the buoy 26 are hollow members, and the cured film is disposed on a resin base material. Since the cured film is disposed on the outside (sea) side of the float 21 and the buoy 26, adhesion of organisms is more easily suppressed even when the float 21 and the buoy 26 are placed in water for a long period of time.

[0144] In the underwater structure 20, the curtains, floats, and buoys have a hardened film formed on their surfaces using the above-mentioned composition, but the underwater structure according to an embodiment of the present invention is not limited to the above, and other parts may have the above-mentioned hardened film.

[0145] Further, while the underwater structure 20 is a pollution prevention membrane, the above is only one example of an underwater structure of the present invention, and underwater structures according to embodiments of the present invention are not limited to the above and may be water supply and drainage outlets of power plants (thermal or nuclear), coastal roads, undersea tunnels, and fishing equipment (ropes, fishing gear such as fishing nets, buoys, etc.), etc.

[0146] [Medical Devices] 4 is a perspective view of a medical device according to an embodiment of the present invention. Medical device 30 is a microchannel chip. Medical device 30 has a flat substrate 31 and a cured film 32 formed on substrate 31. A pattern of recesses 33 is formed on the surface of the cured film 32, and the cured film 32 is configured so that liquid can flow along the recesses. The cured film 32 having a pattern of recesses 33 can be produced by pressing a mold having protrusions of a shape complementary to the pattern of the recesses 33 against a composition layer and curing the layer. In addition, since the composition can be crosslinked by irradiation with light, it can also be patterned using known photolithography techniques.

[0147] The material constituting the substrate 31 is not particularly limited, but examples thereof include resin, glass, etc. The thickness of the film is not particularly limited, but generally, a thickness of 100 nm to 10 mm is preferable.

[0148] In the above medical device, since the recess 33 is formed on the cured film 32, even if the solution to be tested is passed through the recess 33, biological substances are less likely to adhere to the recess 33, enabling more accurate measurements, etc. The above is just one example of a medical device according to an embodiment of the present invention, and the medical device may be another article having the above-mentioned film.

[0149] Other articles may be, for example, cell culture vessels, cell culture sheets, cell capture filters, vials, plastic-coated vials, syringes, plastic-coated syringes, ampoules, plastic-coated ampoules, cartridges, bottles, plastic-coated bottles, pouches, pumps, sprayers, stoppers, plungers, caps, lids, needles, stents, catheters, implants, contact lenses, microchannel chips, drug delivery system materials, artificial blood vessels, artificial organs, hemodialysis membranes, guard wires, blood filters, blood storage packs, endoscopes, biochips, glycosynthesis equipment, molding auxiliary materials, and packaging materials. EXAMPLES

[0150] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0151] (Synthesis of PSTCl (macroinitiator)) 4-(Chloromethyl)styrene (2.0g, 13.1mmol), 4-Cyano-4-(phenylcarbonothioylthio)pentanoic acid (10.1mg, 2.6×10 -2 mmol), AIBN (azobisisobutyronitrile, 2.6 mg, 10.5 × 10 -3 The mixture was adjusted to 100 mmol) under an argon atmosphere and stirred in an oil bath at 70°C for 3 hours. After the reaction, the molecular weight and molecular weight distribution were determined by DMF-based GPC measurement. The molecular weight and molecular weight distribution were determined by PST (polystyrene) conversion: Mn=29600, PDI (Poly Dispersity Index)=1.2. PSTCl was purified by reprecipitation using methanol, a poor solvent.

[0152] [ka]

[0153] (P2 (bottle brush) synthesis 1) N-(2-hydroxypropyl acrylamide) (HPA) (0.4 g, 3.1 mmol), the macroinitiator (PSTCl) synthesized above (Mn = 29600, 7.6 mg, 5.0 × -2 mmol), free initiator (Banzyl chloride) (1.56 mg, 1.24 × 10 -2 mmol), Tris[2-(dimethylamino)ethyl]amine(Me6TREN)(28.5mg, 1.24×10 -1 mmol), Cu(I)Cl (6 mg, 6.2 × 10 -2 DMF / MeOH (0.95g / 0.40g) containing 100 mmol of dimethylformamide was prepared in a glove box and stirred in a 30°C oil bath for 1.5 or 3 hours. After polymerization, the molecular weight and molecular weight distribution were determined by DMF-based GPC (PST conversion). The polymerization rate was determined by NMR. Table 1 shows the number average molecular weight and molecular weight dispersity of the obtained bottle brush.

[0154] [ka]

[0155] [Table 1]

[0156] In Table 1, "Free polymer" refers to a specific polymer, and "Bottle Brush" refers to a "bottle brush" polymer. In addition, in Table 1, the initiation efficiency is nearly 100% based on the polymerization rate predicted from the free polymer area and the polymerization rate determined by NMR.

[0157] The graft density of the bottle brush in Example 1 is 0.28 chains / nm 2 (Surface occupancy rate is 0.24), and the graft density of the bottle brush in Example 2 is 0.21 chains / nm 2(The surface area coverage was 0.18).

[0158] (Bottlebrush Synthesis 2) HPA (2.0 g, 15.5 mmol), macroinitiator (PSTCl) (Mn = 29600, 47 mg, 3.1 × 10 -1 mmol), Me6TREN (14.27mg, 6.2×10 -1 mmol), Cu(I)Cl (31 mg, 3.1×10 -1 DMF / MeOH (4.75g / 1.98g) containing 1.0 mmol of dimethylformamide was prepared in a glove box and stirred in a 30°C oil bath for 3 hours. After polymerization, the molecular weight and molecular weight distribution were determined by DMF-based GPC (PST conversion). The obtained bottle brush was purified by reprecipitation recovery using acetone. Table 2 shows the number average molecular weight and molecular weight dispersity of the obtained bottle brush.

[0159] [Table 2]

[0160] The graft density of the bottle brush in Example 3 is 0.13 chains / nm 2 (Surface occupancy is 0.11), and the graft density of the bottle brush in Example 4 is 0.18 chains / nm 2 (The surface area coverage was 0.16). In addition, the “conversion” of Example 3 and Example 4 is 0.40 and 0.27, respectively, the degree of polymerization is 20 and 14, respectively, and σ eff are 0.13 and 0.18, respectively.

[0161] In addition, σ eff represents the "effective graft density (the graft density on the outermost surface of the bottle brush)" and is defined by the following formula.

[0162]

number

[0163] In the above formula, DP n,graft represents the degree of polymerization, and a 2 represents the monomer cross-sectional area, which is 0.86 nm for HPA. 2 It is.

[0164] [Synthesis of P1] The HPA / benzophenone acrylamide (BPA) / AIBN molar ratio was (200-x) / x / 0.2 (x is shown in Table 3), and polymerization was carried out in an oil bath at 70°C in DMF under an argon atmosphere for 1.5 hours. After the reaction, the molecular weight and molecular weight distribution were determined by DMF-based GPC measurement. The obtained polymer was purified by reprecipitation recovery using acetone. 1 It was confirmed by HNMR that the contents of HPA and BPA in the polymer chain were almost equal to the charging ratio. Table 3 shows the composition, abbreviation, number average molecular weight, and molecular weight dispersity of the polymerized polymers (Examples 5 to 7).

[0165] [ka]

[0166] [Table 3]

[0167] [Creating a hardened film] Ethanol solutions containing 3 mass% of P1 of Examples 5 to 7 and P2 (bottle brush) of Example 3 were prepared. Using these, compositions were prepared and films were formed. Table 4 shows the contents of P1 and P2 in the compositions. For example, the composition of Example 8 means that the composition was prepared using P1 of Example 5 without using a bottle brush, i.e., an ethanol solution of P2 (i.e., simply using a 3 mass% ethanol solution of P1 of Example 5). The above is similar for Examples 9 and 10.

[0168] Example 11 means that a composition was prepared by mixing a 3 mass% solution of P1 of Example 5 with a 3 mass% solution of P2 (bottle brush) of Example 3 at a mass ratio of 1:1. The above is the same for Examples 12 to 14.

[0169] These compositions were spin-coated onto a PET (polyethylene terephthalate) film (3000 rpm, 30 seconds). The spin-coated film was cured by irradiating with ultraviolet light for 3 minutes. The cured film was immersed in ethanol and water and washed. It was confirmed that there was no change in film thickness before and after washing. Table 4 shows the water contact angles of these cured films at 25°C.

[0170] [Table 4]

[0171] [Experiment for immersion in artificial seawater] An immersion experiment was conducted using artificial seawater for breeding marine fish ("Instant Ocean", manufactured by Aquarium Systems Inc.). PET film (diameter 2 cm) 2 The compositions of Examples 8 to 14 were spin-coated on the substrate and cured by UV irradiation. The substrate was then washed with ethanol and air-dried to obtain a cured film. The substrate was then placed in each well of a 24-well multi-well plate, and 1 ml of artificial seawater was added. The artificial seawater was replaced every 2 to 3 days.

[0172] (film thickness measurement) The thickness of the cured films was measured using an ellipsometer after immersion in seawater for 0 months (M0), 1 month (M1), 2 months (M2), and 3 months (M3). Five samples were prepared for each composition, and the film thickness was averaged. Figures 5 to 7 show the test results. No reduction in film thickness was observed for any of the cured films. Figures 5 to 7 show the change over time (horizontal axis, months) in film thickness (vertical axis, units of nm) of the cured films prepared using each composition.

[0173] [Biofouling prevention performance under exposure to salt water (1)] The biofouling inhibition performance was evaluated in a saline exposure environment using mouse fibroblast cells. PET film (2cm) with cured film laminated 2 ) in a Falcon (registered trademark) 24-well multiplate (1 well = ca 2 cm 2 ) and sterilized with 70% ethanol. After sterilization, the samples were washed five times with PBS (Phosphate Buffered Saline). Next, mouse fibroblast cells (L929) were cultured at 50,000 cells / cm. 2 After 24 hours, the samples were washed three times with PBS, and the adherent cells were fixed with 4% paraformaldehyde. The cell nuclei were stained blue with DAPI (4',6-diamidino-2-phenylindole), and the cytoskeleton was stained red with phalloidin, and observed under a fluorescent microscope. It was confirmed that the number of cells adhered to TCPS (Tissue-culture-treated polystyrene) was almost the same as the number of cells seeded. Figures 8 to 10 show the test results. Figure 8 shows the number of adherent cells for each sample after 0 months of immersion, Figure 9 shows the number of cells after 1 month of immersion, and Figure 10 shows the number of cells after 2 months of immersion.

[0174] In the figure, the vertical axis "Adherent L929 cells / %" indicates the number of adherent cells as a percentage when the number of cells adhered to the PET film is taken as 100%. 8 to 10 show that the cured films of the compositions of the present invention, Examples 12 and 13, can maintain excellent biofouling inhibition performance for a long period of time even under exposure to saline water, compared with Examples 8 and 9. "nd" indicates that no biofouling was detected.

[0175] [Biofouling prevention performance under exposure to salt water (2)] The biofouling inhibition performance was evaluated using Cyprus larvae in a saline exposure environment. 2100 cypris larvae were seeded on the coatings of Examples 9 and 13, and the adhesion form and number of adhesions after 15 days were observed. A glass plate was prepared as a reference sample. Figure 11 shows the juvenile barnacles adhered to each surface. In Figure 11, barnacles were attached to the areas surrounded by white circles in the coatings of Examples 9 and 13. Note that a large number of barnacles were attached to the glass substrate on the left of Figure 11. Barnacles were attached to the areas that look like white dots in the image. Note that white circles are not drawn on the glass substrate.

[0176] The ratio of attached juvenile barnacles (per 100 seeds) is shown in Figure 12. It was confirmed that attachment of juvenile barnacles was suppressed on the bottle brush-containing coating surface.

[0177] [Biofouling prevention performance in seawater exposure environment] The biofouling control performance was evaluated in a seawater exposure environment using Cyprus larvae.

[0178] First, the bottle brush (P2) was prepared in the same manner as above. Table 5-1 shows the types of bottle brushes prepared. Among them, the bottle brush of Example 17 was used in the following experiments.

[0179] [Table 5-1]

[0180] (Sample preparation) An ethanol solution containing 3% by mass of each of P1 of Example 6 and P2 of Example 17, and a polyvinyl chloride (PVC) film (30×30×0.5 mm, transparent) were prepared.

[0181] Next, each sample was prepared as described in Table 5-2. First, in Examples 21 and 22, the above PVC film was used as is. In Examples 23 and 24, the P1 solution of Example 6 was used to spin coat (3000 rpm, 30 seconds) a PET (polyethylene terephthalate) film, and the film was irradiated with ultraviolet light for 3 minutes to obtain a film. In Examples 25 and 26, the P1 solution of P6 and the P2 solution of Example 17 were used to spin coat (3000 rpm, 30 seconds) a PET (polyethylene terephthalate) film, and the film was irradiated with ultraviolet light for 3 minutes to obtain a cured film. In Examples 27 and 28, a glass plate was used.

[0182] The cured film was immersed in ethanol and water for cleaning. It was confirmed that there was no change in film thickness before and after cleaning. Table 5 summarizes the samples used.

[0183] [Table 5-2]

[0184] (Preparation of test organisms) We used the attachment stage larvae (cypris) of the barnacle Acanthurus fasciatus, which attach in large numbers to artificial structures in inland bays. Adult barnacles (produced off the coast of Himeji) were maintained and raised in a circulating tank (water temperature 23±1℃) by feeding them Artemia. Nauplius larvae that hatched from the adults were collected and transferred to a glass beaker filled with filtered seawater, and raised on floating diatoms (Cheatoceros calcitrans), to artificially obtain attachment stage larvae (cypris larvae) (Figure 13). The obtained cypris larvae were maintained in a cool and dark environment. These larvae were returned to room temperature before the test, and actively swimming individuals were selected and used in the attachment test.

[0185] (Test Method) The samples were placed on the bottom of a polypropylene container (111 x 81 x 46 mm) and seawater and attached stage larvae were added. Natural seawater collected from the coast of Himeji city was filtered through a mixed cellulose membrane with a pore size of 0.45 μm (Toyo Roshi Co., Ltd.) for use (salt concentration 2.86%, pH 8.06). Approximately 100 larvae were placed in each test container and observed for 9 days at room temperature of around 25°C, under light (laboratory lighting) during the day and in the dark at night.

[0186] (result) First, the results of Example 21 and the control (untreated vinyl chloride film) of Example 22 will be described. In both Examples 21 and 22, the test larvae were actively swimming and engaged in searching for the sample (one of the attachment behaviors) from the start of the test, but attachment to the sample was observed 7 days after the start of the test. In Example 21, one juvenile barnacle was observed, and at the end of the test (9 days later), there were 18 juvenile barnacles and 10 metamorphosing barnacles, for a total of 28 barnacles (28.3%) attached. In Example 22, after 7 days, 3 juvenile barnacles and 2 metamorphosing barnacles were observed, and at the end of the test (after 9 days), there were 61 juvenile barnacles and 10 metamorphosing barnacles, for a total of 71 (72.4%). The final attachment rate, calculated as the average of these, was 50.4%. Figures 14 and 15 are images of the entire surface of the samples at the end of the tests in Examples 21 and 22. The black dots in the images are juvenile barnacles attached to the sample surface. The following table shows the details of the results.

[0187] [Table 6]

[0188] Next, the results of Examples 23 and 24 will be described. In both Examples 23 and 24, the test larvae were actively swimming from the start of the test, but little exploration of the samples was observed until 7 days after the start of the test. Attachment was confirmed 9 days after the test ended. In Sample Example 23, there was one juvenile barnacle and two metamorphosing barnacles, and in Sample Example 24, there was one juvenile barnacle and one metamorphosing barnacle. The final attachment rate, calculated as the average of these, was 2.3%. 16 and 17 are images of the entire sample surface at the end of the test in Examples 23 and 24. The following table provides details of the results.

[0189] [Table 7]

[0190] Next, the results of Examples 25 and 26 will be described. In both Examples 25 and 26, the test larvae were actively swimming from the start of the test, but no exploration behavior or attachment to the sample was observed, and the final average attachment rate was 0%. 18 and 19 are images of the entire sample surface at the end of the test in Examples 25 and 26. The following table provides details of the results.

[0191] [Table 8]

[0192] Next, the results of Examples 27 and 28 will be described. This test area was established to confirm the morphology and behavior of the test larvae, as well as their attachment and metamorphosis processes. Attachment was observed five days after the start of the test, and gradually increased, with 106 and 102 juvenile barnacles observed at the end of the test. The final attachment rate, averaging these, was 97.2%. In the glass plate control area, no abnormalities were observed, particularly in the attachment, metamorphosis, or behavior of the cypris larvae, and the attachment rate was high at 97.2%, confirming that the cypris larvae were capable of attaching normally. Figures 20 and 21 are images of the entire sample surface at the end of the test in Examples 27 and 28. The following table provides details of the results.

[0193] [Table 9]

[0194] Fig. 22 is a graph showing the number of cypris larvae attached to each sample. From the results in Fig. 22, it was confirmed that the cured films of Examples 25 and 26 have excellent biofouling inhibition performance in a seawater environment.

[0195] [Long-term stability] To predict the long-term stability of the cured film, we investigated the hydrolysis resistance of the polymer brush. In a saline exposure environment, the stability of the cured film may decrease due to the progress of hydrolysis of the polymer compound that constitutes the cured film. Here, for example, if the polymer brush has high hydrolysis resistance, it can be predicted that the cured film will have excellent long-term stability.

[0196] (Synthesis of methacrylate-based macroinitiator (PBIME)) A methacrylate macroinitiator and a methacrylate bottle brush were synthesized according to the following scheme.

[0197] BIEM (2-(2-bromoisobutyryloxy)ethyl methacrylate, 5.0 g, 17.9 mmol), cumyl dithiobenzoate (48.8 mg, 1.79 × 10 -1 mmol), 2,2′-Azobis(isobutyronitrile)(AIBN)(5.88mg, 3.58×10 -2 A toluene solution (50 mass%) containing 1,2-dichlorophenyl ether (mmol) was prepared under an argon atmosphere and stirred in an oil bath at 60°C for 22 hours. After the reaction, the molecular weight and molecular weight distribution were determined by DMF-based GPC measurement. The PMMA-equivalent Mn was 18,300 and PDI was 1.16. The polymerization rate was determined by NMR measurement to be 52% (polymerization degree 52). PBIEM was produced by reprecipitation recovery using methanol, a poor solvent (yield 2.61 g).

[0198] [ka]

[0199] (Synthesis of methacrylate-based bottle brushes) An anisole solution (31.58 g, 33 mass%) containing Poly(ethylene glycol) methyl ether methacrylate (PEGMA) (15.79 g, 31.6 mmol), macroinitiator (PBIEM) (Mn = 18300, 0.2938 g, 1.05 mmol (bromine terminal)), dNbipy (4.4-dinonyl-2.2-dipyridyl, 0.8604 g, 2.1 mmol), Cu(I)Br (0.1611 g, 1.1 mmol), and Cu(II)Br2 (0.0502 g, 0.2246 mmol) was prepared in a glove box and stirred in a 65 °C oil bath for 40 min.

[0200] After polymerization, the molecular weight and molecular weight distribution were determined by DMF-based GPC (PMMA equivalent). The polymerization rate was determined by NMR. The results are shown in Table 10. The graft density was 0.318 chains / nm. 2 (surface occupancy rate of 0.92), which confirmed that this was in the dense polymer brush region. After polymerization, the bottle brush was purified by reprecipitation recovery with a hexane / diethyl ether = 70 / 30 mass / mass% solution. Table 10 shows the synthesis results. In Table 10, the polymerization degree was calculated from the conversion assuming an initiation efficiency of 100%.

[0201] [Table 10]

[0202] [Hydrolysis test] The hydrolysis resistance of the bottle brush of Example 15 and the bottle brush of Example 29 was evaluated. First, 1M sodium hydroxide and 1M hydrochloric acid were prepared using heavy water for NMR. The bottle brush polymers of Example 15 and Example 29 represented by the following formula were dissolved (2.0 mass%) in each solution in Table 11. NMR measurement was then performed immediately (time 0 h), and the NMR tube was immersed in a water bath at 80°C, and after 3 hours (3 h) and 6 hours (6 h), the temperature was returned to room temperature and NMR measurement was performed. In addition, the solution after 6 hours of heating was collected and GPC measurement was performed. The samples dissolved in 1M sodium hydroxide and 1M hydrochloric acid were neutralized before being used for GPC measurement.

[0203] [ka]

[0204] (Confirmation of structural changes by NMR measurement) Figures 23 and 24 are NMR charts of polyHPA bottle brush (acrylamide type, Example 15) and polyPEGMA bottle brush (methacrylate type, Example 29) that were heat-treated in 1M sodium hydroxide solution. Almost no peak shift was observed in the polyHPA bottle brush (Example 15) (Figure 23), but a peak shift was observed in the polyPEGMA bottle brush (Example 29) (Figure 24, around 3.35 and 3.1 ppm).

[0205] Figures 25 and 26 are NMR charts of PolyHPA bottle brush (acrylamide type, Example 15) and PolyPEGMA bottle brush (methacrylate type, Example 29) that were heat-treated in 1M hydrochloric acid. A new peak appeared at about 3.7 ppm in the polyHPA bottle brush (Example 15), but otherwise almost no changes were observed (Figure 25). In contrast, a peak shift was observed in the polyPEGMA bottle brush (Example 29), similar to alkaline decomposition (Figure 26, around 3.1 ppm).

[0206] (Confirmation of molecular weight change by GPC measurement) After heat treatment (hydrolysis reaction) in acid or alkali for 6 hours, GPC measurements were performed on the polyHPA bottle brush (acrylamide type, Example 15) and the polyPEGMA bottle brush (methacrylate type, Example 29). Figures 27 to 32 are GPC charts.

[0207] Figures 27 to 29 show the results for polyHPA bottle brush (Example 15). Figure 27 shows the result after 6 hours in heavy water (in the figure, "D2O" stands for heavy water), Figure 28 shows the result after 6 hours in 1M sodium hydroxide solution, and Figure 29 shows the result after 6 hours in 1M hydrochloric acid. From the above results, it can be seen that in either case of acid or alkali treatment, the peak (top) hardly shifted at all. This result 1 The results were almost identical to those of HNMR.

[0208] Figures 30 to 32 show the results for polyPEGMA bottle brush (Example 29). Figure 30 shows the result after 6 hours in heavy water, Figure 31 shows the result after 6 hours in 1M sodium hydroxide solution, and Figure 32 shows the result after 6 hours in 1M hydrochloric acid. From the above results, it was found that the peak shifted significantly to the lower molecular weight side in the case of alkali treatment. It is considered that the molecular weight became smaller because the carbonyl groups of the macroinitiator and the PEGMA monomer were hydrolyzed in the alkali treatment, and the graft polymer itself or the side chains of PEGMA (PEG) were liberated. From the above results, it was confirmed that acrylamide-based polymers have superior hydrolysis resistance compared to (methyl)acrylate-based polymers.

[0209] [Synthesis of DOPA monomer] Dopamine hydrochloride (8.0g, 42.2mmol) and triethylamine (4.3g, 42.5mmol) were dissolved in methanol and stirred on ice. To this solution, a tetrahydrofuran solution (4ml) containing methacryl chloride (5.29g, 50.8mmol) and a methanol solution containing triethylamine were alternately dropped (adjusted so that the pH of the solution was 9.5 or higher). After reacting at room temperature for 18 hours, the solvent was removed using an evaporator. 300ml of ethyl acetate was added thereto, washed twice each with 1M HCl and saline, dehydrated with Na2SO4, and then the ethyl acetate was removed using an evaporator. The resulting impurities were purified by recrystallization to obtain the target compound, N-(3,4-dihidroxyphenetyl) methacrylamide (DOPA monomer) (yield 3.4g, 26%).

[0210] [Synthesis of poly(HPA-BPA-DOPA)] The synthesized DOPA monomer was used to synthesize "poly(HPA-BPA-DOPA)". HPA, BPA, and DOPA monomers were polymerized in an argon atmosphere in a DMF oil bath at 70°C for 3 hours in a molar ratio of HPA / BPA / DOPA = 85 / 5 / 10. After the reaction, the PMMA-equivalent molecular weight and molecular weight distribution were determined by DMF-based GPC measurement (Mn = 89,000, PDI = 2.2). The resulting polymer was purified by reprecipitation recovery using acetone. The structure of poly(HPA-BPA-DOPA) is as shown in the formula below, and the numbers to the right of each unit indicate the mole percentage of each unit.

[0211] [ka]

[0212] [Adhesion evaluation to silicon substrate] An ethanol solution containing 3% by mass of a binary copolymer (HPA / BPA=95 / 5) (polymer of Example 6) or a ternary copolymer (HPA / BPA / DOPA=85 / 5 / 10) was spin-coated onto a silicon substrate and an aluminum plate (rotation speed 3000 rpm, 30 seconds). Then, ultraviolet light was irradiated for 4 minutes to form a crosslinked film. Then, the film was immersed in ethanol for 1 hour and washed.

[0213] Figure 33 is a photograph showing the state of a cured film made of a binary copolymer (HPA / BPA=95 / 5), and Figure 34 is a photograph showing the state of a cured film made of a ternary copolymer (HPA / BPA / DOPA=85 / 5 / 10) before and after cleaning. There was no change in the appearance of either cured film before and after cleaning. This shows that the coating film made of the above copolymer has excellent adhesion to silicon substrates.

[0214] Figure 35 shows a binary copolymer (HPA / BPA=95 / 5), and Figure 36 shows a ternary copolymer (HPA / BPA / DOPA=85 / 5 / 10) used for film formation on an aluminum substrate, and the hardened films after washing are photographed. In both cases, hardened films with excellent surface properties were obtained.

[0215] The thickness of the crosslinked film on the silicon substrate measured by an ellipsometer before and after cleaning is shown in Table 11. As a result, the thickness of each copolymer was almost unchanged before and after cleaning.

[0216] [Table 11]

[0217] In Table 11, the unit of film thickness is nm.

[0218] Next, the crosslinked film on the silicon substrate was immersed in ethanol and ultrasonically cleaned. It was confirmed that the crosslinked film of the binary copolymer (HPA / BPA=95 / 5) began to peel off from the substrate one minute after ultrasonic cleaning (Figure 37). On the other hand, no peeling was observed for the ternary copolymer (HPA / BPA / DOPA=85 / 5 / 10) (Figure 38). This confirmed that copolymers using DOPA are more stable when applied to the surface of substrates that do not contain hydrocarbons (metal substrates, etc.).

[0219] [Cell adhesion test] An aluminum plate and a PET film were spin-coated (3000 rpm, 30 seconds) with an ethanol solution containing only the terpolymer or the terpolymer and the bottle brush of Example 17 at 3% by mass, followed by UV irradiation (4 minutes) to form a crosslinked film.

[0220] Each sample (1×1cm 2 ) in a Falcon 24-well multiplate (1 well = ca 2 cm 2 ) and sterilized with 70% ethanol. Mouse fibroblast cells (L929) were then cultured at 50,000 cells / cm. 2 were seeded onto the samples. After 24 hours, the samples were washed three times with PBS (phosphate-buffered saline) and the adherent cells were fixed with 4% paraformaldehyde. The cell nuclei were stained blue with DAPI (4',6-Diamidino-2-phenylindole) and the cytoskeleton was stained red with phalloidin, and observed under a fluorescent microscope. It was confirmed that the number of cells adhered onto TCPS (Tissue-culture-treated polystyrene) was almost the same as the number seeded. The results are shown in Figure 39.

[0221] In FIG. 39, "TCPS" indicates the number of cells adhered to a TCPS substrate. "PET" indicates the number of cells adhered to a polyethylene terephthalate (PET) substrate. "BB mix on PET" indicates the number of cells adhered to a cured film formed on a PET sheet using an ethanol solution containing 3% by mass of the terpolymer and the bottle brush of Example 17. "Al" indicates the number of cells adhered to an Al substrate. "Terpolymer" indicates the number of cells adhered to a terpolymer. "BB mix on Al Plate" indicates the number of cells adhered to a cured film formed on an Al substrate using an ethanol solution containing 3% by mass of the terpolymer and the bottle brush of Example 17. It was confirmed that the crosslinked film containing the bottle brush significantly suppressed cell adhesion compared to the sample not containing the bottle brush.

[0222] [Adhesion test of cypris larvae] Various polymers were applied and fixed to a polyvinyl chloride (PVC) film (30 x 30 x 0.5 mm, transparent) using the same method as above (spin coating, UV irradiation). The crosslinked film was immersed in ethanol and water and washed. Next, the effect of each surface (Table 12) on inhibiting the attachment of cypris larvae was examined using the attached stage larvae of the barnacle (cypris larvae). The bottle brush used was that of Example 17. Furthermore, the test was carried out with N=2 for each sample.

[0223] [Table 12]

[0224] (Test organism (striped barnacle, attached larvae)) We used the attachment stage larvae (cypris) of the barnacle Acanthurus fasciatus, which attach in large numbers to artificial structures in inland bays. Adult barnacles (produced off the coast of Himeji) were maintained and raised in a circulating tank (water temperature 23±1℃) by feeding them Artemia. Nauplius larvae that hatched from the adults were collected and transferred to a glass beaker filled with filtered seawater, and raised on the floating diatom Cheatoceros calcitrans to artificially obtain attachment stage larvae (cypris larvae). The obtained cypris larvae were maintained in a cool and dark environment. These larvae were returned to room temperature before the test, and actively swimming individuals were selected and used in the attachment test.

[0225] (Test method and test conditions) The samples were placed on the bottom of a polypropylene container (111 x 81 x 46 mm), and seawater and the attachment stage larvae were added. Natural seawater collected from the coast of Himeji City was filtered through a mixed cellulose membrane with a pore size of 0.45 μm (Toyo Roshi Co., Ltd.) for use (salt concentration 2.86%, pH 8.06). Approximately 100 larvae were placed in each test container, and observation and attachment tests were performed for 9 days at room temperature of around 25°C, under light (laboratory lighting) during the day and in the dark at night.

[0226] (Control (untreated polyvinyl chloride film)) In both cases 30 and 31, the test larvae were actively swimming and searching for the sample (one of the attachment behaviors) from the start of the test. Attachment to the sample was observed 3 or 7 days after the start of the test. In case 30, 5 juvenile barnacles were confirmed after 7 days, and 13 juvenile barnacles (13.0%) were attached at the end of the test (9 days later). In case 31, 1 juvenile barnacle and 2 metamorphosing barnacles were confirmed after 3 days, and 17 juvenile barnacles and 1 metamorphosing barnacle were confirmed at the end of the test (9 days later), for a total of 18 barnacles (19.0%). The final attachment rate, averaging these, was 16.0%. In addition, 4 thoracic limbs protruded and were unresponsive in sample 1-1 and 13 in sample 1-2. Attachment to the test container was confirmed at the end of the test (9 days later). Table 13 shows the results, and Figure 40 shows a photograph of juvenile barnacles (whole sample) attached to the sample surface at the end of the test.

[0227] [Table 13]

[0228] (HPA / BPA / DOPA=85 / 5 / 10) In both cases 32 and 33, the test larvae were actively swimming after the start of the test, but almost no exploration behavior toward the sample was observed until 3 days after the start of the test. Attachment was confirmed after 5 days, and 9 days for cases 32 and 33. At the end of the test, sample 32 had 21 juvenile barnacles and 2 metamorphosing barnacles, while sample 33 had 5 juvenile barnacles and 1 metamorphosing barnacle. The final attachment rate, averaging these, was 14.4%. In addition, 4 thoracic limbs protruded and no reaction were observed in sample 2-2, and 2 in 2-2. Attachment to the test container was confirmed at the end of the test (9 days later). Table 14 shows the results, and Figure 41 is a photograph of juvenile barnacles (whole sample) attached to the sample surface at the end of the test.

[0229] [Table 14]

[0230] (HPA / BPA / DOPA-Bottle Brush) In both Examples 34 and 35, the test larvae were actively swimming from the start of the test, but no exploration behavior or attachment to the samples was observed, and the final average attachment rate was 0%. Individuals with protruding thoracic limbs appeared after 5 days, and at the end of the test there were 4 individuals in Sample 3-1 and 3 individuals in Sample 3-2. Attachment to the test container was confirmed after 7 days. Table 15 shows the results, and Figure 42 is a photograph of juvenile barnacles (whole sample) attached to the sample surface at the end of the test.

[0231] [Table 15]

[0232] (Glass plate control) This test area was established to confirm the morphology and behavior of the test larvae, as well as the attachment and metamorphosis process (Examples 36 and 37). Attachment was observed one day after the start of the test, and gradually increased, with 36 and 38 juvenile barnacles observed at the end of the test. The final attachment rate, averaging these, was 34.5%. Five and six juvenile barnacles showed thoracic limb protrusion and no reaction. Attachment to the test container was confirmed after 7 days. Table 16 shows the results, and Figure 43 is a photograph of the juvenile barnacles (whole sample) attached to the sample surface at the end of the test.

[0233] [Table 16]

[0234] Figure 44 shows the number of attached cypris larvae after 9 days of the attachment test. It was found that the cured films of Examples 34 and 35 suppressed the attachment of cypris larvae. This confirmed that the bottle brush polymer was effective in preventing the attachment of cypris larvae even when a terpolymer containing DOPA was used. [Explanation of symbols]

[0235] 10: Ship 11: Base material 12: Primer layer 13: Cured film 20: Underwater structure 21: Float 22: Curtain 23: Weight 24: Anchor 25: Anchor rope 26: V 40: Medical Devices 41: Base material 42: Cured film 43: Recess

Claims

[Claim 1] A first polymer compound having a repeating unit represented by the following formula 1 and a repeating unit represented by the following formula 2: and a second polymer compound having a repeating unit represented by the following formula 3: 【Chemistry 1】 【change】 【change】 (In formulas 1 to 3, R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group; Z 1 , and Z 3 each independently represents a group having a hydrophilic group, which may be the same or different; Z 2 represents a photoradical generating group, L 1 represents a group represented by formula 4a or 4b; L 2 represents a single bond or a divalent group; R 5 represents a hydrogen atom, a halogen atom, or a monovalent substituent, n represents an integer of 2 or more, and in Formula 4a and Formula 4b, * represents a bonding position.

Citation Information

Patent Citations

  • Carrier for immunoaffinity chromatography and its preparation

    JP1986283345A

  • Capillary coating that can capture analytes

    JP2009544969A

  • Color-converting photonic crystal structure and color-converting photonic crystal sensor using the same

    JP2018536903A

  • Biocompatible material, and biocompatible coating agent

    JP2016210956A